2004
DOI: 10.1111/j.1600-0889.2004.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

A history of atmospheric tritium gas (HT) 1950-2002

Abstract: A B S T R A C T Data collected as a part of this study from and data from other studies from [1950][1951][1952][1953][1954][1955][1956][1957][1958][1959][1960][1961][1962][1963][1964][1965][1966][1967] show that the maximum atmospheric concentration of tritium gas (HT) occurred in the early to mid 1970s, which corresponds to the era of frequent, large underground nuclear tests. These data clearly show that the major source of HT to the atmosphere between 1962 and the early 1990s was the underground testing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Fig. 8 plots data for atmospheric tritium concentration found in the literature (Östlund and Mason, 1985;Okai and Takashima, 1989;Okai et al, 1996Okai et al, , 1999Shinotsuka et al, 2003;Happell et al, 2004;Momoshima et al, 2007;Uda et al, 2008). The presently obtained atmospheric HT and CH 3 T concentrations were most similar to the recently reported values at Toki by Uda et al (2008).…”
Section: Atmospheric Hto Ht and Ch 3 T Concentrationssupporting
confidence: 80%
See 1 more Smart Citation
“…Fig. 8 plots data for atmospheric tritium concentration found in the literature (Östlund and Mason, 1985;Okai and Takashima, 1989;Okai et al, 1996Okai et al, , 1999Shinotsuka et al, 2003;Happell et al, 2004;Momoshima et al, 2007;Uda et al, 2008). The presently obtained atmospheric HT and CH 3 T concentrations were most similar to the recently reported values at Toki by Uda et al (2008).…”
Section: Atmospheric Hto Ht and Ch 3 T Concentrationssupporting
confidence: 80%
“…After the atmospheric HT concentration reached above 100 mBq m 3 in the early 1960's, it gradually decreased in the late 1970's to 1990's. Mason and Östlund (1979) estimated that the apparent half-life of atmospheric HT measured at Miami during 1968e1978 was 4.8 y, and data during the 1980s and 1990s followed this declining trend (Happell et al, 2004). Okai et al (1999) also reported that the apparent half-lives of HT at Fukuoka were 6.5 y for 1988e1992 and 10 y for 1988e1995.…”
Section: Atmospheric Hto Ht and Ch 3 T Concentrationsmentioning
confidence: 99%
“…In 1968,Östlund and Mason started a program using a different sampling technique that measured HT regularly at a number of surface stations (Östlund and Mason, 1974). The measurements at Miami are published until 2002, so that a fairly complete history of the T content in tropospheric H 2 can be constructed (Happell et al, 2004). It shows that the T content continued to increase reaching a broad maximum of about 2.6 × 10 6 TU in 1975.…”
Section: Trend In Htmentioning
confidence: 99%
“…2b). This is due to the presence of tritogenic He, originating from the copious amounts of tritium released into the atmosphere as a result of nuclear weapons testing from the 1950s to 1980s (Happell et al, 2004). This indicates that the water emanating from these springs is less than 50 years old.…”
Section: Heliummentioning
confidence: 99%